Transcutaneous temperature controlled radiofrequency: groundbreaking technology - Female stress urinary incontinence and overactive bladder can be treated noninvasively and with vulvovaginal rejuvenation? - Vineet V Mishra; Smit Bharat Solanki; Nita Vineet Mishra; Red M Alinsod (Wolters Kluwer Medknow Publications, 2023)
It has long been difficult to treat vulvovaginal laxity, genitourinary syndrome of menopause, stress urine incontinence, overactive bladder (OAB), and other indications of sexual dysfunction because women traditionally find it difficult to discuss these difficulties with clinicians and because society generally accepts these diseases. Originating in esthetic medicine, noninvasive feminine rejuvenation that targets vaginal tissue with energy-based methods has recently become more popular. A more youthful-looking vulva, the restoration of vaginal elasticity and "tightness," a significant improvement in stress urinary incontinence, a reduction in symptoms of OAB, and a decrease in sexual dysfunction are all benefits of transcutaneous temperature-controlled radiofrequency (TTCRF) therapy at the vulvovaginal region. It is also becoming more popular as a mild-to-moderate stress urinary incontinence and OAB noninvasive therapy option. Women will likely always be appreciative of their gynecologist for managing stress urinary incontinence with TTCRF therapy without making an incision, it would appear.